Heard on the street. (Economist, 2006)
The article discusses podcasting, which allows audio and/or video clips to be posted to the internet and downloaded, and was popularized by Adam Curry. The "casting" comes from broadcasting, which means sending a radio signal to an entire population in a particular geographic area at a particular time; and "pod" comes from Apple's iPod. Curry's podcast entitled "The Daily Source Code" has millions of listeners. Podcasting's expected impact upon traditional radio is assessed.